Cadaverised girls: the writing of Anna Kavan. Issue 4 (2nd April 2020) - Sweeney, Carole
ABSTRACT: Beginning her career as Helen Ferguson, Anna Kavan published six realist novels before changing her name in 1939–1940 after which she began to write in a more experimental, expressionistic style. Providing an introduction to her work as well as a more detailed consideration of selected fiction, this article reads Kavan's work through Julia Kristeva's idea of melancholia in Black Sun (1989), and suggests that the drive to lifelessness apparent in her writing is an internalisation of what André Green calls the 'dead' mother. For the deadened 'girls' in Kavan's fiction, the damaged relationship to the maternal chora is carried around as the unnamed 'Thing' rendering the child guilty, disconsolate and in constant retreat from the symbolic order.